Compatibility and strategic convergence: military and environmental approaches towards south atlantic brazilian oceanic islands (Revista da EGN, 2023)
Several Marine Protected Areas have been created inthe world, in part to fulfill one of the United NationsConvention on Biodiversity goals as to preserve at least10% of each country’s coastal and marine areas. Thisstudy aims at analyzing military presence in the Brazilianoceanic islands of Fernando de Noronha, Trindade& Martin Vaz and São Pedro & São Paulo and how itinteracts with the environmental approach, since thethree encompass Large Scale Marine Protected Areas.A brief overview about the importance of the islandsto Brazilian geopolitical thinkers is shown, as well asthe theoretical issues regarding the military presencein preserved environmental areas. Those results arethen applied to the three Large Scale Marine ProtectedAreas’ present situation, with the conclusion pointing toa positive feedback loop, with significant and favorableresults on environmental and military approaches, aswell as regarding geopolitical goals.